دور الأنشطة المسرحية في ترقية مهارات التعبير الشفهي في المدرسة المتوسطة الإسلامية - Setiadi, Fadlan Masykura; Harahap, Wilna Syahfutri (Al-Wasil, 2025)
This study aims to explore the implementation of theatrical methods in teaching Arabic to improve students' speaking skills at State Islamic Junior High School 2, Labuhan Batu Selatan, North Sumatra. This study employed a qualitative research method with descriptive analytical approach, the research collected data through interviews with teachers and students, direct observations, and document analysis. The results showed that the implementation of theatrical methods significantly improved students' fluency, confidence, and understanding of the material. This method also created a more interactive and lively learning environment. The success of the theatrical method heavily relies on the active role of the teacher in guiding and motivating students. This study makes an important contribution to the development of Arabic teaching methods by demonstrating that theatrical methods can effectively and contextually enhance students' speaking skills, with potential integration into Arabic language curricula in junior high schools.